Volatile organic compounds (vocs) emitted from 40 mediterranean plant species:: Voc speciation and extrapolation to habitat scale - Owen, S M; Boissard, Christophe; Hewitt, C N (Atmospheric Environment, 2001)
Forty native Mediterranean plant species were screened for emissions of the C5 and C10 hydrocarbons, isoprene and monoterpenes, in ﬁve diﬀerent habitats. A total of 32 compounds were observed in the emissions from these plants. The number of compounds emitted by diﬀerent plant species varied from 19 (Quercus ilex) to a single compound emission, usually of isoprene. Emission rates were normalised to generate emission factors for each plant species for each sampling event at standard conditions of temperature and light intensity. Plant species were categorised according to their main emitted compound, the major groups being isoprene, a-pinene, linalool, and limonene emitters. Estimates of habitat ﬂuxes for each emitted compound were derived from the contributing plant species’ emission factors, biomass and ground cover. Emissions of individual compounds ranged from 0.002 to 505 g ha 1 h 1 (camphene from garrigue in Spain in autumn and isoprene from riverside habitats in Spain in late spring; respectively). Emissions of isoprene ranged from 0.3 to 505 g ha 1 h 1 (macchia in Italy in late spring and autumn; and riverside in Spain in late spring; respectively) and a-pinene emissions ranged from 0.51 to 52.92 g ha 1 h 1 (garrigue in Spain in late spring; and forest in France in autumn; respectively). Habitat ﬂuxes of most compounds in autumn were greater than in late spring, dominated by emissions from Quercus ilex, Genista scorpius and Quercus pubescens. This study contributes to regional emission inventories and will be of use to tropospheric chemical modellers
Keywords: biogenic voc speciation; branch enclosure; extrapolation to regional scale; isoprene emissions; Mediterranean vegetation; monoterpene emissions; volatile organic compounds flux

Effect of habitat and age on variations in volatile organic compound (VOC) emissions from Quercus ilex and Pinus pinea - Street, R A; Owen, S; Duckham, S C (Atmospheric Environment, 1997)
A dynamic branch enclosure was used to measure emission rates of volatile organic compounds (VOCs) under field conditions from two common native Mediterranean species, Quercus ilex and Pinus pinea. In addition to a-pinene, B-pinene, sabinene, limonene and cineole, a suite of lesser known compounds were tentatively identified including cis- and trans-ocimene, cis- and trans-linalool oxide and sabinaketone. Emissions of isoprene from Quercus ilex were insignificant in comparison to those of the monoterpenes and were not detected from Pinus pinea. Variability in emission rates between two habitats, the forest and the dunes, were assessed for Quercus ibex. Temperature sensitivities of emissions and total summed emission rates from Quercus ilex were clearly related to environmental conditions. Emission rates from Pinus pinea showed great variability, but differences between normalised mean emission rates from mature forest and young plantation trees may be significant. Existing emission rate models were found to inadequately describe the observed data.
Keywords: Biogenic emissions; branch enclosure; Mediterranean vegetation; Monoterpene; Pinus pinea; Quercus ilex; VOCs

Screening of 18 Mediterranean plant species for volatile organic compound emissions - Owen, S; Boissard, C; Street, R A; Duckham, S C; Csiky, O; Hewitt, C N (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.
Keywords: Arbutus unedo; Biogenic emissions; branch enclosure; Chrysanthemum praecox; cistus incanus; Cistus salvifolius; Cytisus sp.; Dittrichia sp.; Erica arborea; Erica multiflora; Helichrysum stoechas; isoprene; Juniperus oxycedrus; Juniperus phoenicea; Monoterpene; myrtus communis; Phillyrea angustifolia; Pinus pinea; Quercus cerris; Quercus ilex; Rubus fruticosus; Spartium junceum; VOCs